Sustainable Development, Leadership, and Innovations - Streimikiene, Dalia; Mikalauskiene, Asta.; Čiegis, R. (Milton : CRC Press LLC, 2019)
This book deals with the main challenges of sustainable development and the role of sustainable business and corporate social responsibility in implementing these challenges through sustainable leadership and innovations. It includes the economic, social, and environmental dimensions of sustainability and emphasizes the importance of achieving a socio-environmental balance in society. The theoretical frameworks and insights from sustainable development implementations on macro and micro levels, as well as the practical examples and case studies provided to introduce the concept of sustainable leadership and its impact on sustainable business development, are a scientific novelty in the field of sustainability. The book is comprised of six interconnected chapters that sequentially reveal the principal provisions of sustainable development, corporate social responsibility, and sustainable leadership, together with their correlations. Features: Provides cutting-edge examples and case studies of sustainable leadership, viewed as the most significant means for the creation of sustainable organizational culture Includes case studies on the economic, social, and environmental dimensions of sustainability Addresses scientific aspects of sustainable development and its challenges Discusses issues of sustainable development at different scales, ranging from macro to mirco levels Provides policy implications for sustainable business development The theoretical framework and practical case studies presented in Sustainable Development, Leadership, and Innovations make it an invaluable resource and guide to both the academic and business communities. Business leaders, policy makers, and other professionals, as well as academics and graduate students, will all benefit greatly from this text.
6.4 Goals and Innovations of Sustainable DevelopmentChapter 7 Conclusions; References; Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Sustainable development -- Technological innovations; Leadership; SCIENCE / Environmental Science; BUSINESS & ECONOMICS / Development / Sustainable Development